The Effect of Job Characteristics and Competence on Employee Performance with Organization Culture as a Moderating Variable Studies in the Field of Employment BPJS Membership All over East Java - Adiatma, Hagianto (Universitas Nahdlatul Ulama Sidoarjo, 2023)
The purpose of this research is to analyze the effect of between occupation characteristics of the performance, the influence of competence on the performance, the influence of occupation characteristics with the culture of the organization, the influence of competence with the culture of the organization, the effect of competence work on the employee performance by moderation culture of the organization and the influence of competence on employee performance by moderation organization culture. The research was conducted of employment participation BPJS Ketenagakerjaan in east java with a number of respondents 69 people as a sample. The sampling technique used a method of convenience. Data analysis used validity test with matrix component, alfa cronbach for reliability test, and double regression analysis. From this research, it is known that the occupation characteristics has no effect with the culture organization at BPJS Ketenagakerjaan, competence has a positive effects and significant with the culture organization at BPJS Ketenagakerjaan, occupation characteristics has no effect on the employee performance at BPJS Ketenagakerjaan, competence has a positive and significant effects on employee performance at BPJS Employment regional offices of the east java. Moderation testing shows that cultures organization is a variable moderation in the effect of occupation characteristics and competence on employee performance